Access to fruit and vegetable markets and childhood obesity: A systematic review. (14th January 2020) - Yang, Shujuan; Zhang, Xiao; Feng, Ping; Wu, Tong; Tian, Ruochen; Zhang, Donglan; Zhao, Li; Xiao, Chenghan; Zhou, Zonglei; He, Fang; Cheng, Guo; Jia, Peng
Summary: The lack of access to fruit/vegetable markets (FVMs) is thought to be a risk factor for childhood obesity by discouraging healthy dietary behaviours while encouraging access to venues that offer more unhealthy food (and thus the compensatory intake of those options). However, findings remain mixed, and there has not been a review of the association between FVM access and childhood obesity. A comprehensive and systematic understanding of this epidemiologic relationship is important to the design and implementation of relevant public health policies. In this study, a literature search was conducted in the Cochrane Library, PubMed, and Web of Science for articles published before 1 January 2019 that focused on the association between neighbourhood FVM access and weight‐related behaviours and outcomes among children and adolescents. Eight cross‐sectional studies, two longitudinal studies, and one ecological study conducted in five countries were identified. The median sample size was 2142 ± 1371. Weight‐related behaviours and outcomes were used as the outcome variable in two and eight studies, respectively, with one study using both weight‐related behaviours and outcomes as outcome variables. We still found a negative association between access to FVMs in children's residential and school neighbourhoods and weight‐related behaviours and an inconclusive association between FVM access and overweight or obesity. This conclusion should be regarded as provisional because of a limited amount of relevant evidence and may not be a strong guide for policymaking. Nonetheless, it points to an important research gap that needs to be filled if successful public health interventions are to be undertaken.